1999
DOI: 10.1152/ajpcell.1999.277.2.c233
|View full text |Cite
|
Sign up to set email alerts
|

Tissue factor activity is increased in human endothelial cells cultured under elevated static pressure

Abstract: We tested the hypothesis that elevated blood pressure, a known stimulus for vascular remodeling and an independent risk factor for the development of atherosclerotic disease, can modulate basal and cytokine-induced tissue factor (TF; CD 142) expression in cultured human endothelial cells (EC). Using a chromogenic enzymatic assay, we measured basal and tumor necrosis factor-α (TNF-α; 10 ng/ml, 5 h)-induced TF activities in human aortic EC (HAEC) and vena cava EC (HVCEC) cultured at atmospheric pressure and at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Moreover, circulating monocytes derived from patients with elevated levels of blood pressure were found to express significantly higher levels of the inflammatory cytokines, TNF-a, a TF inducer, and IL-1b, than normal donors, suggesting an activation of these cells in systemic hypertension [3,4]. In the past few years a number of in-vitro studies have demonstrated that the exposure of human endothelial cells to haemodynamic forces may modify the expression of target genes involved in regulating vascular homeostasis, including the TF gene [22][23][24][25]. The human TF gene promoter region contains binding sites for the transcription factor activator protein 1, nuclear factor kappa B/Rel, Egr-1 and Sp-1 [28,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, circulating monocytes derived from patients with elevated levels of blood pressure were found to express significantly higher levels of the inflammatory cytokines, TNF-a, a TF inducer, and IL-1b, than normal donors, suggesting an activation of these cells in systemic hypertension [3,4]. In the past few years a number of in-vitro studies have demonstrated that the exposure of human endothelial cells to haemodynamic forces may modify the expression of target genes involved in regulating vascular homeostasis, including the TF gene [22][23][24][25]. The human TF gene promoter region contains binding sites for the transcription factor activator protein 1, nuclear factor kappa B/Rel, Egr-1 and Sp-1 [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Circulating monocytes isolated from hypertensive individuals have been seen to produce more inflammatory cytokines and have a greater power to adhere to cultivated endothelial cells compared with monocytes obtained from normotensive controls [3,4]. A number of experimental studies have indicated an increase in TF expression and activity in human endothelial cells cultured under altered flow conditions [22][23][24][25], such as shear stress, cyclic strain and elevated static pressure.…”
Section: Introductionmentioning
confidence: 99%
“…TNF-α stimulates TF and PAI-1 production in endothelium. 21,22) IL-6 is induced by TNF-α 23) and has proinflammatory and procoagulant properties. 24) TNF-α and IL-6 are elevated in patients with unstable angina and acute myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Both the HAECs and BAECs used for the experiments described here were pooled from several independent isolations following purification of the primary isolate (to > 99%) by manual weeding and/or flow cytometric sorting [21,22]. Subsequently, in order to minimize the differences between the various isolates, several batches of 2nd-passage cells from three individual preparations each were pooled.…”
Section: Cell Culturementioning
confidence: 99%